STYLISTIC AND CONSTRUCTIONAL SOLUTIONS IN BOOK SERIES DESIGN "FAIRY TALES FROM AROUND THE WORLD" OF THE NATIONAL CHILDREN`S LITERATURE PUBLISHING HOUSE "VESELKA" - Kolosnichenko, M. V.; Krotova, T. F.; Pashkevych, K. L.; Pshinka, N. M. (Art and Design, 2021)
Aim: to analyze the stylistic and constructive features of the design of the books in the series “Fairy Tales from Around the World“ by the publishing house “Veselka“, to trace the sequence of the publishing project and the role of the designer and art-designer in it. Methodology. Historical and comparative methods, as well as art history methods of image and stylistic and formal analysis have been used in the research. Results. The artistic approaches to the creation of 25 books of the series “Fairy Tales from Around the World“ (1978–2016) have been analyzed, the stages of creating the book design of this series have been studied with the help interview of the main artist of the publishing house “Veselka“ (1975–2015), national artist of Ukraine M. Pshinka; the image and stylistic features of this series design have been revealed, which allowed synthesizing the verbal, figurative and architectonic levels of books, ensured the integrity of the book as an artistic object, contributed to the emotional and aesthetic expressiveness of illustrations. Scientific novelty. The image and stylistic features of the decoration of the series “Fairy Tales from Around the World“, founded in 1978 by the National Children's Literature Publishing House “Veselka“, have been analyzed for the first time. The analysis of the books` design in this series as a synthesis of text, illustrations, and layout design has been presented. The sequence of the artistic and production process and the designer`s role in achieving the synergy of visual and verbal images has been traced. The constructive elements of the layout have been analyzed and introduced to ensure the serial stylistic unity of the books, which illustrations were made by different artists, keeping their own bright individual style. Practical significance. The study allowed analyzing the design features of the layout, which due to the creative approach of designers and collaboration with leading Ukrainian illustrators ensured the continued popularity of the books “Fairy Tales from Around the World“ among several generations of young readers, success and awards at numerous international and national competitions over four decades. The construction and serial elements of the layout design, which provided the stylistic unity and recognizability of all books of the series, have been described. The results of the research can be used for further study of the traditions of the art school of illustration and design of Ukrainian books, and also serve as theoretical and visual material in the educational process specializing in “graphic design“.